MODEL OMNIBUS LAW DALAM PENYUSUNAN PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU DI INDONESIA - Alsyam, Alsyam; Syofyan, Yunita (UNES Law Review, 2023)
In the history of the formation of laws and regulations in Indonesia, the Law of the Republic of Indonesia Number 11 of 2020 Concerning Job Creation, is a product of laws and regulations that used the Omnibus Method for the first time in drafting its laws. The Mechanism for Forming Law Number 11 of 2020 refers to Law of the Republic of Indonesia Number 12 of 2011 concerning Formation of Legislation and as amended by Law of the Republic of Indonesia Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning Formation of Legislation, these two laws do not regulate the Omnibus Method. Arrangements related to the new Omnibus Method are included in the Law of the Republic of Indonesia Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 concerning the Formation of Legislation.